Sektor Pariwisata untuk Pemulihan Ekonomi Kalimantan Tengah: Simulasi Tabel Input-Output - Fitri Handayani; Tita Rosy (Jurnal Kebijakan Pemerintahan, 2022)
Abstract The Covid-19 pandemic has had a negative impact on Central Kalimantan's economic growth with a contraction of 1.40 percent in 2020. Central Kalimantan's economic is still highly dependent on natural resource-based sectors, and it will be very vulnerable because the movement of the economy will be greatly influenced by global price volatility and its uncertainty. The tourism sector, therefore, is an important sector that is expected to be an alternative driver sector of economic recovery. This study aims to measure and analyze the relationship between the tourism sector and other sectors, as well as to simulate investment policies in Central Kalimantan. Limited studies that focus on the tourism sector as planning for economic recovery after the pandemic, especially in Central Kalimantan, can make this research as a reference for policy makers in economic planning. The Input Output table released in May 2021 becomes secondary data used in research with forward and backward linkage analysis and investment simulations in the tourism sector. The results showed that the tourism sector is the sector that has the highest forward linkage in Central Kalimantan. Furthermore, if investment is given to the sector of accommodation and food service activities, it will provide the greatest boost to the total economy compared to other tourism sectors. However, the transportation sector which is the infrastructure in tourism also has an important role as a leading sector with more than one forward and backward linkage index. Keywords: Pandemic, Tourism Sector, Economic Recovery, Input Output Table